Metaxanine, A Systemic Fungicide Against Plasmopara Viticola on Wine Grapes: Disease Control, Residues and Effect on Fermentation and Wine Quality - Marais, P. G.; Tromp, A. (South African Journal of Enology and Viticulture, 2017)
The systemic fungicide metaxanine/methyl D, L-N-(2,6-dimethyl-phenyl)-N-(2 methoxyacetyl) alaninate/, was compared with mancozeb for the control of Plasmopara viticola (B x C) Berl. & de T. on grapevines in the Western Cape Province of South Africa. The systemic fungicide gave better control than mancozeb. Good control was obtained with applications of the systemic fungicide at 21 day intervals, despite the fact that weather conditions were particularly favourable for disease development. Residues of metaxanine recovered from grapes were low and did not affect either the onset, or the rate of fermentation of grape juice, nor did it affect wine quality.